Crystal structure characterization of martensite of Cu–Zn–Al ternary alloy by spherical aberration corrected scanning transmission electron microscopy. (October 2021) - Ikeda, Yuki; Nishijima, Masahiko; Kiguchi, Takanori; Konno, Toyohiko J.
Abstract: The crystal structure of martensite in Cu-27at.%Zn-9.0 at.%Al alloy has been studied by using spherical-aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and geometrical phase analysis (GPA) to examine possible changes in atomic rearrangements during martensitic transformation of this ternary system. Observation along [ 100 ] M zone axis is suitable for examining a chemical order of the martensite, and showed that, despite the non-stoichiometry of the alloy, atomic columns containing Al atoms are imaged and distinguished from the others. On the other hand, observation along [ 010 ] M zone axis directly revealed that the parent and martensitic phases possess L21 and 18R ( 2 1 ‾ ) structures, respectively. These observations suggested that the martensite retained the local chemical order of the parent phase without shuffling before and after the transformation. GPA revealed that the interface between the two phases was coherent with tilting of the basal plane approximately 6° across the boundary, which makes otherwise large inclination small during the martensitic transformation. Graphical abstract: Image 1 Highlights: Some Al-sites of the martensite are occupied by Cu atoms. The crystal structure retains chemical order of the parent β phase. The interface is coherent with tilting of the basal plane 6°.